In the footsteps of an unnoticed heritage: Revaluation of the former soap factory in Chepen - Suárez Taboada, Danitza (2026)
The industrial legacy is a historical vestige that preserves the collective memory and is part of a specific environment. The former Chepén soap factory marked key moments over time; its relevance and impact as the headquarters of one of the most important Haciendas in the department of La Libertad. The aim of this research is to understand the valuation of the former soap factory from the perspective of the urban context, allowing heritage recovery. The methodology seeks to find an unnoticed history of the building, creating a superposition of layers through cartographies and historical documents, identifying elements that still exist in time; that allow identifying opportunities to address obsolescence and revalue the industrial complex, concluding to become a milestone element for society, maintaining its distinctive characteristics that involve the community leaving a legacy for future generations.